Primary epidemiological evaluation of the effectiveness of the All-National Dispensarization as a cancer screening by the data of the Arkhangelsk Regional Cancer Registry - L. E. Valkova; M. L. Levit; V. M. Merabishvili; A. Yu. Pankrateva; D. M. Dubovichenko; A. V. Agaeva; A. Yu. Ryzhov; E. F. Potekhina; M. Yu. Valkov (Исследования и практика в медицине)
Purpose of the study. Was to assess the variations of the incidence rate and Stage I proportion of screened malignant neoplasms (MNs) before and after the implementation of All-National Dispensarization of certain groups of the adult population (DCGAP) based on data from the Arkhangelsk Regional Cancer Registry (AOCR).Materials and methods. Anonymous data were taken from the AOCR database about all cases of each of the index MNs (colon, rectum, lung, mammary gland, cervix, uterus, ovary, prostate, and kidney) from 2000 to 2018. The change over time of the number of new cases, crude, age-standardized incidence and the proportion of Stage I, were estimated. The intervention value of the DCGAP was considered positive if a change in the linear trend of selected indicators was detected with segmented regression between 2012 and 2014.Results. The final sample included 46146 cases of MNs. The annual number of new cases and crude incidence for all taken for the analysis MNs from 2000 to 2018 have been increasing. After standardization by age, an increase in incidence was observed for all index MNs, except for lung cancer. In the segmented regression model, this increase for majority MNs was monotonous with an annual percentage change (APC) from 1.5% (for ovarian cancer) to 5.0% (cervical cancer). In prostate cancer, a change of the linear trend of age-standardized incidence with an increase of 8.5% per year was detected in 2012. The proportion of Stage I did not change or increased monotonously after the introduction of DC¬GAP in uterus, ovarian, and colon cancers. An increasing change of the trend of annual Stage I proportion was found in colorectal cancer since 2010, breast cancer since 2011, cervical cancer since 2013, prostate cancer since 2014, kidneys since 2006 with APC by 7.5%, 9, 6%, 9.6%, 40.3%, 13.4%, respectively.Conclusion. Diagnostic tests used in the framework of the DCGAP are sensitive to the detection of early stages of cancer of the breast, cervix, and prostate; for colorectal cancer and kidney cancer, their value is doubtful. The effectiveness of early diagnosis is not confirmed for the lung, uterus, ovarian cancers. For screening-sensitive MNs, an analysis of mortality and survival is necessary.